Faktor Pendorong Perubahan Sikap Politik Luar Negeri Amerika Serikat Terhadap China Terkait Penerapan One China Policy Pada Masa Pemerintaha Presiden Obama (2009 – 2016) - Mahadiyasa, I Gede Mario; Fasisaka, Idin; Parameswari, A.A Ayu Intan (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2017)
ABSTRACT One China Policy brought a dynamic impact on relationship between United State with People Republic of China (China) and Republic of China (Taiwan). United State government’s has taken an ambiguous outlook. United State Government’s more prefer helping Taiwan to prevent threat from China. A change on United State Foreign Policy are then shown in Obama administration. Under Obama Administration, The United State Government’s tried to re-establish the relationship with China and giving advice on Taiwan to make peace with China related to One China Policy. This research analyzes the driving factors behind the changing of United State Foreign Policy outlook toward China in Obama administration related to One China Policy. Data for this study were collected from various sources including: literary sources, news and reports. This analyzes shows that in there are three factor that changes United State Foreign Policy outlook toward China. Those are China rises and China as a new emerging power, economic crisis in 2008 and Asia regional security issue. Keywords : One China Policy, The Changing of Foreign Policy Outlook, Accommodation, Selective Engagement.